20-Day Trend of Serum Potassium Changes in Bam Earthquake Victims with Crush Syndrome; a Cross-sectional Study - Safari, Saeed; Najafi, Iraj; Hosseini, Mostafa; Baratloo, Alireza; Yousefifard, Mahmoud; Mohammadi, Hamidreza (Archives of Academic Emergency Medicine, 2017)
Introduction: Many of those who survive following an earthquake die in the next phase due to preventable and treatable medical conditions such as hyperkalemia. The present study aimed to evaluate the trend of potassium changes in crush syndrome patients of Bam earthquake. Methods: In this retrospective cross-sectional study, using the database of Bam earthquake victims, which were developed by Iranian Society of Nephrology following Bam earthquake, Iran, 2003, the 20-day trend of potassium changes in > 15 years old crush syndrome patients was evaluated. Results: 135 crush syndrome patients with the mean age of 29.9 ± 9.91 years were evaluated (56.3% male). Mean potassium concentration during the first 3 days of admission was 5.6 ± 1.3 mEq/L. On the day of admission, 43.1% (95% CI: 34.0 - 52.2) had normal potassium concentration, 3.4% (95% CI: 0.1 - 6.8) had hypokalemia, and 53.4% (44.3 - 62.6) had hyperkalemia. During 20-day follow-up, 62.3% (95% CI: 66.7-71.9) of the patients had normal potassium. While, 11.5% (95% CI: 9.7-13.3) had hypokalemia and 19.2% (95% CI: 17.0-21.5) had hyperkalemia. As the days of hospitalization increased, prevalence of hyperkalemia decreased while hypokalemia increased. On the 17th day 21.2% (95% CI: 2.2-39.9) had hypokalemia and 10.5% (95% CI: 0.1 – 24.7) had hyperkalemia. Conclusion: Findings of the present study showed that following urine alkalinization and fluid resuscitation, the prevalence of hyperkalemia reduced, but hypokalemia developed. It seems that the correction of serum potassium level should be accompanied by precise monitoring of intake and output of the patient and prescription of reasonable amount of intravenous fluid.